Association of IFNG gene polymorphisms with pulmonary tuberculosis but not with spinal tuberculosis in a Chinese Han population. (October 2017) - Li, Jiong; Zhou, Ying; Zhang, Hongqi; He, Dan; Zhang, Rongmou; Li, Yanbing; Guo, Chaofeng; Guo, Qiang; Wang, Longjie; Yang, Guanteng; Gao, Qile
Abstract: Spinal tuberculosis (STB) is an extrapulmonary form of tuberculosis (TB) caused by Mycobacterium tuberculosis (Mtb), which accounts for around 2% of all TB cases and can lead to spine degeneration. It is widely accepted that host genetic factors participate in the pathogenesis of active TB, but the factors controlling which TB form will manifest after Mtb infection remain unknown. We hypothesized that a genetic difference may exist between the development of STB and pulmonary tuberculosis (PTB). Here, three single nucleotide polymorphisms (SNPs) in the IFNG gene (rs2069718), IRGM gene (rs10065172), and MBL2 gene (rs11003125) were genotyped among 183 PTB patients, 177 STB patients, and 360 healthy controls from the Chinese Han population. We found that rs2069718 genotypes were significantly associated with PTB (TT, p = 0.007; CT, p = 0.008) but not STB, and the TT genotype ( p = 0.046) of rs2069718 were less common in PTB than in STB. In contrast, neither PTB nor STB were found to be associated with rs10065172 and rs11003125. Overall, we found a difference in the rs2069718 genetic distribution between the STB and PTB patients in a Chinese Han population. The rs2069718 TT genotype was associated with a protective role in PTB but not STB development during active Mtb infection. Highlights: The rs2069718 genotypes were significantly associated with PTB but not STB in a Chinese Han population. The TT genotype of rs2069718 was associated with a protective role in PTB but not STB development. Lack of association between rs10065172 or rs11003125 and STB or PTB susceptibility in a Chinese Han population.